The human CAN protein, a putative oncogene product associated with myeloid leukemogenesis, is a nuclear pore complex protein that faces the cytoplasm. - Kraemer, D (1994)
We have carried out partial amino acid sequence analysis of a putative nuclear pore complex protein (nucleoporin) of rat that reacts with wheat germ agglutinin and with the polyspecific monoclonal antibody 414. Surprisingly, these partial amino acid sequence data revealed a high degree of similarity with the human CAN protein, the complete cDNA-derived primary structure of which was reported by Von Lindern et al. [Von Lindern, M., Fornerod, M., van Baal, S., Jaegle, M., de Wit, T., Buijs, A. & Grosveld, G. (1992) Mol. Cell. Biol. 12, 1687-1697]. The CAN protein has been proposed to be a putative oncogene product associated with myeloid leukemogenesis. Its subcellular localization was not established. To confirm that the putative rat nucleoporin is indeed a homolog of the human CAN protein and to determine its subcellular localization, we expressed a 39-kDa internal segment of the 213,790-Da human CAN protein in Escherichia coli and raised monospecific antibodies, which reacted with the putative rat nucleoporin. Immunofluorescence microscopy of HeLa cells gave a punctate nuclear surface staining pattern characteristic of nucleoporins, and immunoelectron microscopy yielded specific decoration of the cytoplasmic side of the nuclear pore complex. This suggests that the protein is part of the short fibers that emanate from the cytoplasmic aspect of the nuclear pore complex. In agreement with previously proposed nomenclature for nucleoporins, we propose the alternative term nup214 (nucleoporin of 214 kDa) for the CAN protein.